2022
DOI: 10.3390/jcm11123359
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Procalcitonin as a Predictor of Long-Term Prognosis in the Early Postoperative Period after Esophagectomy for Esophageal Cancer

Abstract: The aim of this study was to investigate the relationship between serum procalcitonin (PCT) levels after esophagectomy and infectious complications and long-term prognosis. A total of 105 patients who underwent esophagectomy between 2012 and 2019 were stratified into two groups: PCT-High group of ≥1 ng/mL and PCT-Low group of <1 ng/mL. The clinical outcomes and prognostic factors were compared between the two groups 2 postoperative days (POD), 4 POD, and 7 POD after esophagectomy. As the postoperative days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Regarding postoperative PCT-levels, Booka et al conducted a study, analyzing the association between postoperative PCT-levels, PIC and oncological outcome; they identified a prognostic value of 100% of PCT on POD 7 for development of PIC and overall outcome. However, similar to our analysis, they did not find a difference on POD 2 [ 57 ]. Hence, it may be concluded, that later PCT-values are of greater information compared to early PCT-values.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding postoperative PCT-levels, Booka et al conducted a study, analyzing the association between postoperative PCT-levels, PIC and oncological outcome; they identified a prognostic value of 100% of PCT on POD 7 for development of PIC and overall outcome. However, similar to our analysis, they did not find a difference on POD 2 [ 57 ]. Hence, it may be concluded, that later PCT-values are of greater information compared to early PCT-values.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, increased concentrations of serum PCT levels facilitated tumor metastasis and led to poor oncological outcomes [36]. In addition, bacterial toxins including endotoxins could directly stimulate the production of PCT in patients with developing infections, which might also weaken the immune system and facilitate tumor progression [13]. In the present study, a patient with a higher PCT concentration had a significantly worse prognosis no matter whether they developed an infection or not.…”
Section: Discussionmentioning
confidence: 55%
“…In another retrospective study consisting of 95 metastatic NSCLC patients who received immune-check point inhibitors, a baseline PCT concentration of > 0.1 mg/L was confirmed to result in significantly worse outcomes in terms of OS [33]. In contrast, Booka and colleagues [13] reported that in 105 esophageal cancer patients who underwent esophagestomy, a low PCT concentration (< 1 ng/mL) at POD 2 was an independent predictor of poorer OS. Possible explanations for the contradictory conclusions might be the inconsistency of patients inclusion criteria, varied PCT measurement times and the PCT cutoff concentration, relatively small sample sizes and the retrospective nature of the studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations